2014
DOI: 10.1103/physreve.90.042802
|View full text |Cite
|
Sign up to set email alerts
|

Walk-based measure of balance in signed networks: Detecting lack of balance in social networks

Abstract: There is a longstanding belief that in social networks with simultaneous friendly and hostile interactions (signed networks) there is a general tendency to a global balance. Balance represents a state of the network with a lack of contentious situations. Here we introduce a method to quantify the degree of balance of any signed (social) network. It accounts for the contribution of all signed cycles in the network and gives, in agreement with empirical evidence, more weight to the shorter cycles than to the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(113 citation statements)
references
References 28 publications
2
108
1
Order By: Relevance
“…Following this criterion, a network can be divided in blocks; nodes within the same block are positively connected among them while they are negatively connected to nodes in other blocks (Doreian & Mrvar, ). We calculated K using the definition of (Estrada & Benzi, ), K=tr(eboldA)tr(e|A|), where | A | is the underlying unsigned graph of A . High values of K indicate that the network presents a “balanced” structure (with K = 1 indicating a perfect balance), while low values indicate that several links do not fulfil this criterion and network is “unbalanced” (“frustrated,” sensu Doreian & Mrvar, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this criterion, a network can be divided in blocks; nodes within the same block are positively connected among them while they are negatively connected to nodes in other blocks (Doreian & Mrvar, ). We calculated K using the definition of (Estrada & Benzi, ), K=tr(eboldA)tr(e|A|), where | A | is the underlying unsigned graph of A . High values of K indicate that the network presents a “balanced” structure (with K = 1 indicating a perfect balance), while low values indicate that several links do not fulfil this criterion and network is “unbalanced” (“frustrated,” sensu Doreian & Mrvar, ).…”
Section: Methodsmentioning
confidence: 99%
“…Following this criterion, a network can be divided in blocks; nodes within the same block are positively connected among them while they are negatively connected to nodes in other blocks (Doreian & Mrvar, 2009). We calculated K using the definition of (Estrada & Benzi, 2014)…”
Section: Network Indicesmentioning
confidence: 99%
“…Previous studies have shown that social systems (both human and animals) are more balanced (i.e. exhibit less frustration) than is expected by chance, and some have hypothesized that the evolution of the system encourages cooperation and promotes stability by removing these unbalanced links (Szell et al , Facchetti et al , Ilany et al , Estrada and Benzi ). However, the scarcity of real signed networks has hampered the evaluation of this hypothesis in other systems apart from social networks (but see Altafini et al for a similar approach in metabolic networks).…”
mentioning
confidence: 99%
“…Structural balance, one of the most popular properties in ensembles of signed networks, reflects the origin of tensions and conflicts, and its computation and transformation have received much attention from physicist, sociologist, economist, ecologist, ecologist and mathematician [4][5][6][7][8][9][10]. The structural balance theory introduced by Heider states that the relations "the friend of my friend is my enemy" and "the enemy of my enemy is my enemy" are unbalanced in the strong definition, which is based on the statistical analysis of the balance of signed triads from the perspective of social psychology [11].…”
Section: Introductionmentioning
confidence: 99%